Urine Bisphenol A and Arsenic Levels in Residents of the Cheyenne River Sioux Tribe, South Dakota, with and without Diabetes - Chang, Arthur (J Med Toxicol, 2019)
INTRODUCTION: Diabetes disproportionately affects American Indians/Alaskan Natives (AI/AN). Bisphenol A (BPA) and arsenic (As), environmental toxicants which may be associated with diabetes, have not been well studied in this population. Our objectives were to determine if urinary BPA and As are associated with diabetes among adults in the Cheyenne River Sioux Tribe (CRST), and to compare their urinary levels with the general US population. METHODS: We performed a case-control study among 276 volunteers. We matched our cases (persons with diabetes) and controls (persons without diabetes) using age. We collected questionnaire data and urine samples which were tested for BPA and speciated As analytes. We used paired t tests and McNemar’s chi-square test to compare continuous and categorical variables, respectively, between cases and controls and linear regression to assess the association between self-reported exposures and BPA and As levels. We used conditional logistic regression to investigate the association between case status and BPA and As levels. BPA and As levels among participants were compared with those from the 2011–2012 National Health and Nutrition Examination Survey (NHANES). RESULTS: The average age of participants was 46 years. The majority identified as AI/AN race (97%) and 58% were female. The geometric means from CRST participant urine specimens were 1.83 ug/L for BPA and 3.89 ug/L for total As. BPA geometric means of CRST participants were higher than NHANES participants while total As geometric means were lower. BPA and As were not associated with case status. CONCLUSION: The results of this study are consistent with others that have reported no association between diabetes and exposure to BPA or As.